The Conceptual Nexus Between Islamic Foresight, Islamic Thought And The Shariah - Norfadhilah Mohamad Ali; Fadhlina Alias; Hendun Abd. Rahman Shah; Muhammad Nizam Awang; Rana Abu-Mounes (Faculty of Syariah and Law, Universiti Sains Islam, 2024)
Malaysian Journal of Syariah and Law, Volume 12 Issue 1 Page (62–76)